Co-opting or Valuing the Indigenous Voice Through Translation? A Decision for Research Teams - Kidd J; Cassim S; Rolleston A; Keenan R (Wilf Malcolm Institute of Educational Research, 2019)
Although te reo Māori is an official language of Aotearoa New Zealand, translation of research material such as information sheets, consent forms and questionnaires into te reo Māori remains highly variable. Translation tends to occur in research projects where Māori lead the work and that exclusively focus on Māori communities and topics. Translations are not offered or undertaken as a matter of course for all research. As a team of Māori and Indigenous researchers working within the health sector, we believe that there are important questions that need to be explored around the practice of using Indigenous languages, rich in similes and metaphors, to convey English/Western concepts/constructs/ideologies. In this paper, we draw on the story of one project to deconstruct and challenge the hegemonic terms through which translation of research material occurs. We explore the messages that translated material sends to potential research participants. We contend that the choice about whether to translate research material into te reo Māori is one that should be undertaken within a robust decision-making framework that considers the reasons for a translation and its impact on the participants. Translation should not be undertaken primarily to attract Māori participants, but should reliably signal that the research is being undertaken in a way that honours a Māori worldview.